Profit Optimization Based on Total Production in Textile Home Industry Using Evolution Strategies Algorithms - Al Khuluqi, Mabafasa; Mahmudy, Wayan Firdaus; Rahmi, Asyrofa (International Journal of Social and Local Economic Governance, 2016)
Â Profit optimization became one of the main goals of the production process of home industry. A maximum profit can be achieved with proper planning of production. In the process of implementation, production planning has many constraints such as lot sizing, limited stock, overtime work and the many products derived from the same source. To address the problem, we develop computer software using a heuristic method called evolution strategy (ES). ES has capability to solve optimization problems with nearly optimal results. The result of the calculation process of evolution strategy algorithm was compared with data from the source. Computational analysis shows that ES produces a production plan that has profit of Rp 5,324,000. It is bigger than manual production plan that has profit of Rp 2,747,000.Â Keywords: home industry, profit, optimization, production, evolution strategiesÂ